2020
DOI: 10.1111/gcb.15329
|View full text |Cite
|
Sign up to set email alerts
|

Diversity‐dependent soil acidification under nitrogen enrichment constrains biomass productivity

Abstract: The net effects of nitrogen deposition on primary productivity may diminish or accelerate over time if the nitrogen addition also has indirect effects on ecosystem properties that influence productivity. Potential indirect effects of nitrogen addition include declines in biodiversity (Isbell et al., 2013; Komatsu et al., 2019) or changes in abiotic factors like soil pH (Johnston, Goulding, & Poulton, 1986; Lawes & Gilbert, 1880), that then impact productivity. Although the net effects of nitrogen deposition ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 76 publications
3
16
0
Order By: Relevance
“…Second, addition of non-N nutrients, specifically base cations, undoubtedly offset acidifying effects that could have resulted from long-term addition of N alone. Other work at our study site indicates that acidifying effects of chronic N addition can reduce the stimulatory effects of N on productivity (Kimmel et al, 2020). Third, if formation of mineral-associated soil organic matter was co-limited by polyvalent cation and organic matter supply, addition of Ca 2+ and Mg 2+ , along with greater C inputs to soils resulting from higher productivity in fertilized plots, might have synergistically increased formation of stable soil C (Rowley et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Second, addition of non-N nutrients, specifically base cations, undoubtedly offset acidifying effects that could have resulted from long-term addition of N alone. Other work at our study site indicates that acidifying effects of chronic N addition can reduce the stimulatory effects of N on productivity (Kimmel et al, 2020). Third, if formation of mineral-associated soil organic matter was co-limited by polyvalent cation and organic matter supply, addition of Ca 2+ and Mg 2+ , along with greater C inputs to soils resulting from higher productivity in fertilized plots, might have synergistically increased formation of stable soil C (Rowley et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Human activities are considered as the most important causes of acidifying the soil mainly due to the improper input of N fertilizer, deposition of atmospheric N, and fall of acid rain (Raza et al, 2020). The relationships between N management/deposition and soil acidification have been elaborated in the previous studies (Kimmel et al, 2020;Li et al, 2018;Lu et al, 2014;Tian & Niu, 2015). The overall decrease by 1.33 ± 0.28% in soil pH was observed under NT compared to CT by the global meta-analysis of 1059 observations presented herein (Figures 1,2).…”
Section: Soil Acidification Under No-tillmentioning
confidence: 99%
“…A N addition experiment in desert grassland in central New Mexico, USA found that species richness was only affected by inter-annual rainfall changes and not altered by N enrichment, while ANPP was related to the interaction between inter-annual and N addition (Ladwig et al 2012). But in many grassland ecosystems, the addition of water and nutrients tended to reduce community heterogeneity and increase ANPP (Chalcraft et al 2008;Isbell et al 2013;Kimmel et al 2020). The Urat desert grassland is located in an arid and semi-arid marginal area of northwest Inner Mongolia (Luo et al 2020;Luo et al 2018).…”
Section: Introductionmentioning
confidence: 99%